Development of sensor based on electrochemical impedance spectroscopy for the detection of Vitamin D3 using molecularly imprinted polymer@MoSe2 nanosheets - A. Archana; Sandhya Rani Majhi; Harshulika Singh; Pratima R. Solanki (Discover Electrochemistry)
Abstract Vitamin D is a fat-soluble, a secosteroid hormone that is formed when the skin is exposed to sunlight and is essential for the growth and maintenance of healthy bones. It also plays a major role in muscle functioning, cell growth, etc. Vitamin D exits in two forms mainly Vitamin D3 and Vitamin D2 both of which can be obtained from diet or through sun exposure. In this work, an electrochemical sensor based on molecular imprinted polymer (MIP) technique has been devised utilizing polydopamine@MoSe2 nanosheet for the efficient detection of Vitamin D3. The characterizations of the fabricated MIP-based sensor are achieved by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy, and cyclic voltammetry. The electrochemical sensing was performed using electrochemical impedance spectroscopy. The linear range for the detection of Vitamin D3 was 25–200 ng/mL with a LOD of 0.69 ng mL−1 and sensitivity of 133 Ω (ng/mL)−1 cm−2. Also, the interference studies along with the control studies were performed to establish the validity of the fabricated sensor.